(3eHGOF GdeMGSHI hJWHjbGJgG (B/s - (3GdYfGJj, QVhGf eMeOs ((3YeGf(B: s (3OGQ UaGA ddfTQ(B, s, 2000)
(3eONd Edi Yde GdeMGSHI, GdeHGOF GdeMGSHjI, GdfXGe GdeMGSHj, GdeaGgje GdeMGSHjI, fXGe GdbjO GdeROhL, GdeYGdLI GdeMGSHjI ddYedjGJ GdeGdjI hGdGSJKeGQjI, GdeYGdLI GdeMGSHjI dYedjGJ GdHVGYI hGdNUe, GdChQGb GdJLGQjI heYGdLJgG GdeMGSHjI, ejRGf GdeQGLYI hGdCNWGA GdeMGSHjI, GdbhGFe GdeGdjIs
(3GdeQGLY U(B.223s
Keywords: (3GdeMGSHIs; (3eQGLYI GdMSGHGJs